Convolution Operations on Coding Metasurface to Reach Flexible and Continuous Controls of Terahertz Beams. Issue 10 (7th July 2016) - Liu, Shuo; Cui, Tie Jun; Zhang, Lei; Xu, Quan; Wang, Qiu; Wan, Xiang; Gu, Jian Qiang; Tang, Wen Xuan; Qing Qi, Mei; Han, Jia Guang; Zhang, Wei Li; Zhou, Xiao Yang; et al.
Abstract : The concept of coding metasurface makes a link between physically metamaterial particles and digital codes, and hence it is possible to perform digital signal processing on the coding metasurface to realize unusual physical phenomena. Here, this study presents to perform Fourier operations on coding metasurfaces and proposes a principle called as scattering‐pattern shift using the convolution theorem, which allows steering of the scattering pattern to an arbitrarily predesigned direction. Owing to the constant reflection amplitude of coding particles, the required coding pattern can be simply achieved by the modulus of two coding matrices. This study demonstrates that the scattering patterns that are directly calculated from the coding pattern using the Fourier transform have excellent agreements to the numerical simulations based on realistic coding structures, providing an efficient method in optimizing coding patterns to achieve predesigned scattering beams. The most important advantage of this approach over the previous schemes in producing anomalous single‐beam scattering is its flexible and continuous controls to arbitrary directions. This work opens a new route to study metamaterial from a fully digital perspective, predicting the possibility of combining conventional theorems in digital signal processing with the coding metasurface to realize more powerful manipulations of electromagnetic waves. Abstract : Convolutions are operated on 2‐bit coding metasurfaces to reach the steering of scattering pattern to an arbitrarily predesigned direction. The radiation angle can be continuously designed in the entire upper‐half space by simply combining two or multiple gradient coding sequences from a 2‐bit coding metasurface which has only four different coding digits.